Comprehensive Analysis of the Expression Profiles of Hepatic lncRNAs in the Mouse Model of Alcoholic Liver Disease - Dou, Xiaobing; Yang, Wenwen; Ding, Qinchao; Han, Qiang; Qian, Qianyu; Du, Zhongyan; Fan, Yibin; Wang, Cui; Li, Songtao (Frontiers in Pharmacology, 2021)
Background and Aim: The worldwide prevalence of alcoholic liver disease (ALD) due to escalating alcohol consumption has presented an unprecedented pressure on human health. A few studies have determined long non-coding RNAs (lncRNAs) involved in the pathogenesis of liver diseases. However, the roles of lncRNAs in ALD development is still poorly understood. Methods: An ALD mouse model was established and confirmed. Expression profiles of lncRNAs were obtained by whole transcriptome sequencing. The altered lncRNAs in ALD mice were further verified by qRT-PCR. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were used to enrich the functions of these lncRNAs. In combination with miRNA and mRNA profiles, we constructed concise endogenous RNA (ceRNA) networks. The function of the most up/downregulated lnRNA signaling was further verified and investigated in both ALD model and AML-12 cells. Results: Totally, five downregulated lncRNAs were obtained and verified in ALD mice. The GO term and KEGG pathway analyses revealed that the identified lncRNAs were associated with alcohol-induced hepatic oxidative damage, cellular inflammation, and lipid metabolism. Integration the differentially modulated miRNAs and mRNAs with ceRNA network analysis, we constructed five ceRNA networks and screened out 30 miRNAs and 25 mRNAs that may participate in ALD. Further, we verified and investigate the function of the most downregulated lnc_1700023H06Rik. Depletion lnc_1700023H06Rik reduced genes related to lipid metabolism, especially mRNA Acat2 (ENSMUST00000159697) and Pgrmc2 (ENSMUST00000058578) in both ALD mice and AML12 cell. Knocking down lnc_1700023H06Rik induced triglyceride accumulation and LDH leakage in AML12 cells, consisting with that in alcohol-treated cells, confirming the potential pathological role of lnc_1700023H06Rik in ALD. Conclusion: The five remarkably downregulated lncRNAs in an ALD mouse model were identified as novel biomarkers, highlighting the key role of lncRNAs in the development of ALD. The effect of lnc_1700023H06Rik was further verified.